Determinants of family takaful demand among Muslims in the East Coast of peninsular Malaysia - Juliana Arifin
Family Takaful is one of the services sectors that continue to play an important role in supporting economic and social development of Malaysia. However, the penetration rate for Takaful market in Malaysia is still low compared to other Islamic countries such as Sudan, Egypt and Pakistan. For example, it was reported that as at 2012 the total family Takaful contribution was only at RM5.89 million compared to the total of life insurance premium of RM36.7 millions. Thus, the penetration rate for family Takaful is very low compared with life insurance. Many previous studies examine various dominant factors affecting the demand for life insurance and family Takaful. Most of these studies focused on demograhic and economic variables. However, other factors such as religious adherence, reputation and image of Takaful companies, product and services and marketing and advertising are also perceived important. These factors, however were not examined properly by previous researchers. Therefore, this study contributes to the existing literature through the addition of four new variables in the family Takaful demand model among Muslims on the East Coast of Peninsular Malaysia. The objectives of this study include the following three items: First, to identify the determinant of family Takaful demand among Muslim customers on the East Coast of Peninsular Malaysia. Second, to analyze the relationships between determinants with family Takaful demand among Muslim customers on the East Coast of Peninsular Malaysia. Third, to determine the best determinant factors for Family Takaful demand among Muslims customers on the East Coast of Peninsular Malaysia. To achieve all these objectives, a set of questionnaire which contains 45 items were used and divided into six parts. Items used in this study were adapted from Adnan (2010), Hammond et al. (1967), and Mohd Zain (2000). This study involved 243 Muslim respondents who were customers of family Takaful in leadingTakaful companies on the East Coast of Peninsular Malaysia. Reliability test, descriptive statistics, T-test, ANOVA, correlation analysis, and regression analysis were used to analyze the data. This study showed that there were significant differences between all demographic factors and family Takaful demand. The findings of the correlation analysis proved that all the dimensions of religious adherence, reputation and image, product and services, and marketing and advertising have a positive relationship with the demand for the family Takaful. Meanwhile, the result of regression analysis showed that only the dimensions of religious adherence such as faith and belief, obligatory Islamic practices, highly recommended non-obligatory Islamic practices, and reputation and image were the key factors that influence family Takaful demand among Muslim customers in Malaysia. Therefore, the findings of this study provide valuable insights and fill gaps in the Family Takaful literature. At the same time, the results of this study will contribute significantly to the Takaful companies and policy-makers to how surged family Takaful penetration. Finally, future research should involve Muslims customers in all Takaful companies in Malaysia to obtain better results and may also be carried out in depth study by interviewing Muslim customers to get more information why they joined the family Takaful plan.